Prognostic Values of Tissue and Serum Angiogenic Growth Factors Depend on the Phenotypic Subtypes of Colorectal Cancer - Kasurinen Jussi Herman; Hagström Jaana; Kaprio Tuomas; Jalkanen Sirpa; Salmi Marko; Böckelman Camilla; Haglund Caj (MDPI, 2025)
Simple Summary In this study, we showed that the prognostic value of serum concentrations and the tissue expressions of angiogenic growth factors VEGF, bFGF, and PDGF-bb vary according to the phenotypic subtype of the tumor. Patients were classified into phenotypic subgroups (immune, canonical, metabolic, and mesenchymal). Preoperative serum concentrations and tissue expressions of VEGF, bFGF, and PDGF-bb were determined among each phenotypic subgroup. A high tissue expression and serum concentration of angiogenic growth factors seem to indicate improved prognosis among the metabolic subgroup. Among immune patients, a high VEGF serum concentration is associated with worse prognosis. Moreover, a high serum concentration of bFGF indicated improved prognosis among canonical patients. We classified colorectal cancer (CRC) patients into four phenotypic subgroups and investigated the prognostic value of angiogenic growth factors across subgroups. Preoperative serum concentrations and tissue expressions of VEGF, bFGF, and PDGF-bb were determined among 322 CRC patients. We classified patients into phenotypic subgroups (immune, canonical, metabolic, and mesenchymal) according to a method described in our earlier work. Among the metabolic subgroup, patients with high serum concentrations of VEGF, bFGF, or PDGF-bb exhibited a significantly improved prognosis. Moreover, those with high VEGF tissue expressions exhibited a significantly improved prognosis among patients in the metabolic subgroup. Among immune patients, a high VEGF serum expression is associated with a worse prognosis. A high serum bFGF concentration is associated with a favorable prognostic factor among patients with a canonical tumor phenotype. A high PDGF-bb tissue expression is associated with non-metastasized disease and with the immune, canonical, and metabolic subtypes. To our knowledge, this is the first study to show that the prognostic value of angiogenic growth factors differs between phenotypic subtypes.